Evaluation of Studies on Positive Behavior Support Interventions - Uslu, Rukiye (2020)
Positive behavioral support is an approach that uses the principles of applied behavior analysis and system changes to improve individuals' quality of life and reduce problem behaviors. In positive behavior support, it is aimed to determine the functions of the problem behaviors of the child and to gain appropriate behaviors that meet the same functions. This study aims to provide an overview of the studies on positive behavior support through a comprehensive literature review and determine the current trends in the studies on positive behavior support interventions. A total number of 53 studies were examined in the study according to year of publication, country, journal, subject, research method, research sample, data collection tools, data analysis method, type of document, research sample, sample size and authors’ study interests. Data were analyzed with content analysis method and results were presented with frequency and percentages in tables and figures. Results were discussed with relevant literature and recommendations for further research and practices were provided.